A manager's guide to information systems & technology - Shim, Jae K. (Hawkhurst, Cranbrook, Kent : Global Professional Publishing, 2010)
The book provides a wealth of current, essential information on the choice and practical implementation of information systems (IS) and information Technology (IT) in every kind of business.
Includes index.
oif 13/06/13
Loans
Keywords: Information resources management; Information systems; Information technology